The HST/WFC3 Quicklook Project: A User Interface to Hubble Space Telescope Wide Field Camera 3 Data. Issue Volume 12:Issue S325(2016) (30th May 2017) - Bourque, Matthew; Bajaj, Varun; Bowers, Ariel; Dulude, Michael; Durbin, Meredith; Gosmeyer, Catherine; Gunning, Heather; Khandrika, Harish; Martlin, Catherine; Sunnquist, Ben; Viana, Alex
Abstract: The Hubble Space Telescope's Wide Field Camera 3 (WFC3) instrument, comprised of two detectors, UVIS (Ultraviolet-Visible) and IR (Infrared), has been acquiring ~ 50-100 images daily since its installation in 2009. The WFC3 Quicklook project provides a means for instrument analysts to store, calibrate, monitor, and interact with these data through the various Quicklook systems: (1) a ~ 175 TB filesystem, which stores the entire WFC3 archive on disk, (2) a MySQL database, which stores image header data, (3) a Python-based automation platform, which currently executes 22 unique calibration/monitoring scripts, (4) a Python-based code library, which provides system functionality such as logging, downloading tools, database connection objects, and filesystem management, and (5) a Python/Flask-based web interface to the Quicklook system. The Quicklook project has enabled large-scale WFC3 analyses and calibrations, such as the monitoring of the health and stability of the WFC3 instrument, the measurement of ~ 20 million WFC3/UVIS Point Spread Functions (PSFs), the creation of WFC3/IR persistence calibration products, and many others.